2018
DOI: 10.1364/osac.1.001068
|View full text |Cite
|
Sign up to set email alerts
|

Circular intensity differential scattering (CIDS) scanning microscopy to image chromatin-DNA nuclear organization

Abstract: Circular dichroism imaging has proved a powerful and simple method for extracting information on chiral molecules without specific fluorescent labels. Numerous mathematical models show that outside the absorption band, the circular dichroism signal comes from the scattering interaction and brings additional information about the organization of biopolymers. With this article, we propose a fast method to control the polarization states without moving parts, by means of a photoelastic modulator. We implemented t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

7
1

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 28 publications
(40 reference statements)
0
34
0
Order By: Relevance
“…From longer nucleosome arrays to chromatin fiber, other super-resolution techniques, such as Photoactivated Localization Microscopy (PALM) have been used to extrapolate chromatin topology in FIGURE 3 | As with modeling approaches, in experiments different techniques are required to study different orders of magnitude in chromatin: (A) NCP imaged with Cryo-Em (adapted from Kobayashi et al, 2019), (B) NCPs with histone tails AFM image (Filenko et al, 2012), (C) Nucleosome array, AFM image (adapted from Krzemien et al, 2017), (D) Isolated Hek nucleus imaged with CIDS (a), labeled with Hoechst for chromatin-DNA organization imaging. The fluorescence labeling (b) is used as a fingerprint of chromatin to demonstrate the correlation with the label-free approach using circular polarization excitation (Le Gratiet et al, 2018).…”
Section: Experimental Studies Of Chromatin: From the Nucleosome To Thmentioning
confidence: 99%
See 1 more Smart Citation
“…From longer nucleosome arrays to chromatin fiber, other super-resolution techniques, such as Photoactivated Localization Microscopy (PALM) have been used to extrapolate chromatin topology in FIGURE 3 | As with modeling approaches, in experiments different techniques are required to study different orders of magnitude in chromatin: (A) NCP imaged with Cryo-Em (adapted from Kobayashi et al, 2019), (B) NCPs with histone tails AFM image (Filenko et al, 2012), (C) Nucleosome array, AFM image (adapted from Krzemien et al, 2017), (D) Isolated Hek nucleus imaged with CIDS (a), labeled with Hoechst for chromatin-DNA organization imaging. The fluorescence labeling (b) is used as a fingerprint of chromatin to demonstrate the correlation with the label-free approach using circular polarization excitation (Le Gratiet et al, 2018).…”
Section: Experimental Studies Of Chromatin: From the Nucleosome To Thmentioning
confidence: 99%
“…the nucleus from nucleosome dynamics. Label-free techniques are also used to study chromatin at the nuclear level, such as Circular Intensity Differential Scanning (CIDS) in Le Gratiet et al (2018). In this work, it is shown that the main advantage of this polarimetric method compared to standard fluorescence microscopy is the capability to obtain specific contrast mechanisms due to the chiral organization of the DNA in a label-free approach without a priori knowledge of the sample.…”
Section: Experimental Studies Of Chromatin: From the Nucleosome To Thmentioning
confidence: 99%
“…Due to the flexibility of this method and its local sensitivity to optical anisotropy at the nanoscale level, CD/CIDS scanning microscopy has been demonstrated recently as an important tool for label-free imaging in a large range of applications such as for metamaterials characterization [ 133 , 134 , 135 , 136 , 137 ] or chiral polymers organization under certain constraints [ 129 , 138 , 139 ]. Finally, the versatility of this method has shown its potentiality for multimodal imaging of chromatin characterization proposed recently by our group [ 130 ]. We implemented a CIDS imaging modality into a commercial scanning confocal fluorescence microscope in order to observe isolated HEK cell nuclei that were marked with Hoechst 33342, a chromatin binding fluorophore.…”
Section: Cids Microscopy Configurationmentioning
confidence: 99%
“…( b ) Optical microscope using one photoelastic modulator synchronized with a lock-in amplifier and an XY translating sample holder, inspired by [ 100 , 126 , 127 ]. ( c ) Optical scanning microscope using a photoelastic modulator synchronized with a lock-in amplifier, inspired by [ 128 , 129 , 130 ]. PC: Pockels Cell.…”
Section: Figurementioning
confidence: 99%
“…From longer nucleosome arrays to chromatin fibre, other super-resolution techniques, such as Photoactivated Localization Microscopy (PALM) have been used to extrapolate chromatin topology in the nucleus from nucleosome dynamics. Label-free techniques are also used to study chromatin at the nuclear level, such as Circular Intensity Differential Scanning (CIDS) (51). SAXS and Cryo-EM have also been used in structural analysis of the fibre up to the chromosome level (52)(53)(54)(55).…”
Section: Experimental Studies Of Chromatin: From the Nucleosome To Thmentioning
confidence: 99%